2020
DOI: 10.1002/bem.22274
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of the Effects of Tumor‐Treating Electric Fields on Single Cells

Abstract: Tumor-treating fields (TTFields) are low-intensity and intermediate-frequency alternating electric fields that have been found to inhibit tumor cell growth. While effective, the mechanism by which TTFields affect cell growth is not yet clearly understood. Although numerous mathematical studies on the effects of electromagnetic fields on single cells exist, the effect of TTFields on single cells have been analyzed less frequently. The goal of this study is to explore through a mathematical analysis the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…A second piece of evidence supporting TTFields’ effects on cell membranes comes from finite element modeling in which a modified Schwan equation was the governing model for membrane depolarization (along with the Laplace equation for electric field distribution). Li et al [ 51 ] predicted that TTFields depolarize the cell membrane by 10-17%, which may be enough to open membrane Ca v 2+ channels [ 51 ] and, at TTFields’ frequency, would likely ‘freeze’ the channels in an open state.…”
Section: Results: Explanatory Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…A second piece of evidence supporting TTFields’ effects on cell membranes comes from finite element modeling in which a modified Schwan equation was the governing model for membrane depolarization (along with the Laplace equation for electric field distribution). Li et al [ 51 ] predicted that TTFields depolarize the cell membrane by 10-17%, which may be enough to open membrane Ca v 2+ channels [ 51 ] and, at TTFields’ frequency, would likely ‘freeze’ the channels in an open state.…”
Section: Results: Explanatory Modelsmentioning
confidence: 99%
“…Various studies have shown the effectiveness of using irreversible electroporation to induce tumor ablation and suggest that its ability to target malignant cells is due to plasma membrane differences between cancer and non-cancer cells [ 67 , 68 ]. The V m of both non-cancer and cancer cells depolarizes during proliferation, to about −15 mV, but post-mitotic non-cancer cells return to a typical resting V m of −70 mV whereas post-mitotic cancer cells achieve a resting V m of −25 mV [ 51 , 69 ]. The depolarized resting V m in cancer cells relative to that in non-cancer cells is thought to be caused by altered lipid and sterol membrane composition, which results in an influx of sodium ions into the cell and a collection of negative charges on the cell coat [ 70 ].…”
Section: Results: Explanatory Modelsmentioning
confidence: 99%
See 3 more Smart Citations